Comparison of Brain Natriuretic Peptide Levels to Simultaneously Obtained Right Heart Hemodynamics in Stable Outpatients with Pulmonary Arterial Hypertension - Scott A. Helgeson (Diseases, 2018)
Pulmonary arterial hypertension (PAH) is a progressive disease that requires validated biomarkers of disease severity. While PAH is defined hemodynamically by right heart catheterization (RHC), brain natriuretic peptide (BNP) is recommended by guidelines to assess disease status. Retrospectively collected data in 138 group 1 PAH patients were examined for the correlation of BNP levels to simultaneously obtained right heart catheterization (RHC). Patients were mostly Caucasian women, with functional class III symptoms, mean BNP of 406 ± 443 pg/mL, and an average right atrial pressure (RAP) of 9.9 ± 5.7 mm Hg and mean pulmonary artery pressure (mPAP) of 47.3 ± 14.7 mm Hg. Significant correlation was demonstrated between BNP and RAP (p = 0.021) and mPAP (p = 0.003). Additional correlation was seen with right heart size on echocardiography: right atrial (RAE; p = 0.04) and right ventricular enlargement (p = 0.03). An increased BNP level was an independent predictor of mortality (p < 0.0001), along with RAP (p = 0.039) and RAE (p = 0.018). Simultaneous collection of BNP at the time of RHC confirmed the correlation of BNP with right heart hemodynamics. The current results reinforce the use of BNP level as a continuous variable to assess disease severity in group 1 PAH.